MiR-143-3p suppresses tumorigenesis in pancreatic ductal adenocarcinoma by targeting KRAS - Fei Xie; Chuan Li; Xiaoyun Zhang; Wei Peng; Tianfu Wen (2019)
Pancreatic ductal adenocarcinoma (PDAC) is a malignant tumor with high mortality and metastasis, which is difficult to diagnose and treat. MicroRNA-143-3p (miR-143-3p) acts as a tumor suppressor in various cancers. However, its role in pancreatic ductal adenocarcinoma has not been explored. Here we examined the potential role and mechanism of miR-143-3p in PDAC.The levels of miR-143-3p and KRAS mRNA in matched PDAC and normal tissues as well as PDAC cell lines were determined by quantitative RT-PCR. The effect of miR-143-3p on cell proliferation was evaluated by Cell Counting Kit-8 assay, colony-forming assay and a mouse subcutaneous transplantation model. Transwell assay, wound healing assay and a mouse orthotopic implantation model were conducted to examine the role of miR-143-3p on cell migratory and invasive capacities. The target gene and mechanisms of miR-143-3p were explored by qRT-PCR, western blot and luciferase assays.The expression of miR-143-3p was down-regulated in PDAC tissues compared with the paired adjacent normal tissues. Cell proliferative, migratory and invasive capacities in PDAC cells were significantly decreased by miR-143-3p up-regulation. Moreover, we identified KRAS as a direct target of miR-143-3p, revealed its expression to be inversely correlated with miR-143-3p in PDAC samples. Up-regulated expression of KRAS partially reversed the phenotypes induced by miR-143-3p overexpression. What's more, KRAS could activate the ERK signaling pathway, which is associated with tumorigenesis.MiR-143-3p may suppress tumorigenesis in PDAC by targeting KRAS. This might provide a theoretical basis for miR-143-3p in treatment of pancreatic cancer.